2007
DOI: 10.4141/p06-135
|View full text |Cite
|
Sign up to set email alerts
|

Plant species diversity, ecosystem function, and pasture Management—A perspective

Abstract: 2007. Plant species diversity, ecosystem function, and pasture management-A perspective. Can. J. Plant Sci. 87: 479-487. Grassland farmers face many challenges in pasture management including improving sustainability, reducing inputs of fertilizers and pesticides, and protecting soil resources. In this paper we provide our perspective on managing plant diversity within and among pastures as one tool to aid producers in meeting these challenges. Pasture ecosystems can be highly diverse, with a complex array of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 54 publications
1
64
1
1
Order By: Relevance
“…Overyielding in these studies was attributed to N fixation by legumes, niche complementarity, and resource use efficiency in mixtures. Sanderson et al (2007) also suggest that diversity in perennial forage stands provides yield stability where stresses such as drought occur and where there is variability in soils, landscape, and climate. As such, perennial polyculture adds a degree of resilience to agricultural systems.…”
Section: Perennial Crops In Rotationmentioning
confidence: 99%
“…Overyielding in these studies was attributed to N fixation by legumes, niche complementarity, and resource use efficiency in mixtures. Sanderson et al (2007) also suggest that diversity in perennial forage stands provides yield stability where stresses such as drought occur and where there is variability in soils, landscape, and climate. As such, perennial polyculture adds a degree of resilience to agricultural systems.…”
Section: Perennial Crops In Rotationmentioning
confidence: 99%
“…Multifunctional grassland management seeks to provide a large number of ecosystem services (Sanderson et al, 2007;Lemaire et al, 2005), including ecological processes that have been shown to be more effective with increasing species diversity (Balvanera et al, 2006;Cardinale et al, 2006;Diaz et al, 2006;Hector and Bagchi, 2007). At present, multifunctionality is primarily achieved at the landscape or farm level, with high-intensity plots managed for productivity, and low-intensity plots managed for conservation of biodiversity and ecosystem services on more marginal sites.…”
Section: Implications For Multifunctional Grassland Managementmentioning
confidence: 99%
“…Current and future management goals recognise the benefits of multifunctionality in grassland agriculture providing a large number of ecosystem services (Sanderson et al, 2007;Lemaire et al, 2005). These services include ecosystem processes with direct functional benefits in an agricultural context such as yield, decomposition, nutrient leaching, pollination, soil conservation and resistance to weed invasion along with forage stability under changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, other additional ecosystem functions as enhancement of carbon sequestration or mitigation of greenhouse gas emissions should be considered by farmers as a way of capitalizing new opportunities to diversify the forage-livestock system (Lemaire, 2007, Sanderson et al, 2007. However returning to the first page of this chapter we remember that degradation processes in tropical grassland are advancing over wide areas through overgrazing on poor soils.…”
Section: Discussionmentioning
confidence: 99%